2011
DOI: 10.1080/17461391.2011.583991
|View full text |Cite
|
Sign up to set email alerts
|

Supervised slackline training improves postural stability

Abstract: The present study investigated whether or not four weeks of supervised slackline training (SLT) performed on nylon webbing improves postural stability. Twenty-four healthy adults participated in the study and were assigned to either SLT (n 012) or a control (CON) group (n012). The SLT group completed a four week training program, while the CON group received no training. Centre of gravity (COG) and joint angles (ankle, knee and hip) were calculated using whole body three-dimensional (3D) kinematic measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
4
36
0
4
Order By: Relevance
“…It was, for example, shown that skiing (Lauber et al, 2011) and in-line skating (Taube et al, 2010) in elderly people are adequate means to improve postural stability. The same effect was observed when young adults (students) participated in slackline training (Keller et al, 2012;Pfusterschmied et al, 2013). Thus, it is possible to observe an enhanced postural control after several weeks of alternative balance training both when tested on the training device itself, but also when tested in a postural transfer test.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…It was, for example, shown that skiing (Lauber et al, 2011) and in-line skating (Taube et al, 2010) in elderly people are adequate means to improve postural stability. The same effect was observed when young adults (students) participated in slackline training (Keller et al, 2012;Pfusterschmied et al, 2013). Thus, it is possible to observe an enhanced postural control after several weeks of alternative balance training both when tested on the training device itself, but also when tested in a postural transfer test.…”
Section: Discussionmentioning
confidence: 65%
“…A custom-built joystick potentiometer was connected to the platform for the evaluation of the sway path of the platform in antero-posterior and medio-lateral (ml) direction. The same device was used in different recent publications (Taube et al, 2010;Keller et al, 2012;Pfusterschmied et al, 2013) and was shown to provide good test-retest reliability for different age groups (Boeer et al, 2010). It has to be mentioned, however, that none of the age groups evaluated by Boeer et al (2010) corresponded to the age group used in the present study.…”
Section: Measurements Conducted In the Pre-and Post-testmentioning
confidence: 99%
See 2 more Smart Citations
“…In children as well as in young and older adults, slackline training was shown to improve the ability to balance on the slackline (Granacher et al 2010;Donath et al 2013;Pfusterschmied et al 2013;Gabel et al 2015;Donath et al 2016). Based on these positive results and the relatively low costs and large variety of possible exercises, slackline-based training is finding its way into fitness and therapeutic settings (Gabel et al 2013).…”
Section: Introductionmentioning
confidence: 99%